Cistatinas de maqui: produção recombinante e inibição de cisteíno peptidases - Souza, Eduardo Pereira de (2022)
Cystatins are tight binding competitive inhibitors of cysteine peptidases. In plants, they act regulating different physiological mechanisms, as well as defending from biotic and abiotic stresses, making them of potential use for biotechnological applications in agriculture. In humans, cystatins are associated with the control of cysteine-cathepsins, which, when deregulated, can trigger distinct pathologies. Then, the intervention with exogen cystatins, like the phytocystatins, have been studied as a therapy for cancer or inflamatory diseases, for example. In the face of the wide variety of cystatins applications, the search for new variants in different plant species is relevant. The maquiberry (Aristotelia chilensis) is a native plant from South America, closely related to the Chilean culture. Recently, it has been coming into light due to its high anthocyanin content, and now the species is considered a superfruit. As an understudied species, little is known about the biotechnological potential of its proteins, until then, underinvestigated. In light of this, this work consisted in the identification, recombinant production and characterization of maquicystatins. From a trascriptome of the plant cultivated in Temporary Immersion Bioreactor, six sequences were identified, from which five were obtained by cDNA amplification. These were cloned in pET-28a expression vector for production in Escherichia coli Rosetta (DE3). The purified proteins were submitted to fluorimetric assays of inhibition against cysteine peptidases. All cystatins were able to inhibit papain with Ki of 7.13, 1.42, 3.29, 2.99, 5.05 nM, for MaquiCPIs 1 to 5, respectively, proving that they were expressed in the right conformation. They were also able to inhibit human cathepsin L efficiently (Ki of 0.34, 0.33, 0.38, 0.57 and 1.25 nM), but only MaquiCPIs 1, 2 and 3 could inhibit human cathepsin B (Ki of 35.74, 20.97 e 21.94 nM, respectively) in nanomolar order, while the others inhibited the protein in micromolar order. The capacity of maquicystatins in inhibiting human cathepsin indicates a potential in controlling distinct pathologies.